PERAN MAHASISWA KKM 57 DESA PARIGI DALAM PENGUATAN LITERASI ANAK MELALUI PROGRAM MEMBACA NYARING - Umroh Umroh; Febrianti Satibi; Fikri Nur Alim; Gumelar Saktiana; Andriansah Andriansah; Frisky Friendly Jovial; Tb.Moch Riad All Fariz; Febryanna Rachmawati; Nova Eliza; Putri Sabrina; Shifa Hafizha Safira; Meidita Sabrina; Jihan De Sabilla; Syarif Abdullah (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Literacy skills serve as a fundamental pillar in supporting children's cognitive and socio-emotional development. Unfortunately, disparities in access to literacy resources remain prevalent, particularly in rural areas such as Parigi Village. The read-aloud program initiated by KKM 57 student volunteers emerged as a strategic effort to cultivate a joyful and inclusive reading habit among children in the community. This study adopts a descriptive qualitative approach to provide an in-depth account of the program's implementation and its impact on children's motivation and engagement in literacy activities. Data were collected through observations, interviews, and documentation during activities held at the "Desaku Cerdas" Community Library. The findings indicate that the read-aloud method successfully created a welcoming and interactive learning environment, increased children's confidence to express themselves, and encouraged parental involvement in supporting children's reading habits. These outcomes reinforce the idea that simple yet participatory approaches like reading aloud can be effective alternatives in promoting community-based literacy culture. Therefore, similar programs are worth replicating in other areas with appropriate contextual adaptations. Keywords: literacy, reading aloud, KKM 57